2014
DOI: 10.1007/s40120-014-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Post Hoc Analysis of Nutritional Status in Patients with Transthyretin Familial Amyloid Polyneuropathy: Impact of Tafamidis

Abstract: IntroductionGastrointestinal symptoms are common among patients with transthyretin familial amyloid polyneuropathy (TTR-FAP). This post hoc analysis evaluated the nutritional status of TTR-FAP patients treated with tafamidis while enrolled in clinical trials.MethodsNutritional status was measured by the modified body mass index (mBMI = BMI × albumin level). Treatment-related changes in mBMI were reported for 71 Val30Met TTR-FAP patients who completed an 18-month, randomized, double-blind, placebo-controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Compared with the worsening observed during the 18-month placebo phase, TQOL remained relatively stable during long-term tafamidis treatment in ATTRV30M patients and was comparable to that observed in the patients who had received tafamidis from study start. Nutritional status as assessed by mBMI remained relatively stable during long-term tafamidis treatment, which is consistent with published analyses by Suhr et al [33], and lends further support for the long-term efficacy of tafamidis in slowing disease progression.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with the worsening observed during the 18-month placebo phase, TQOL remained relatively stable during long-term tafamidis treatment in ATTRV30M patients and was comparable to that observed in the patients who had received tafamidis from study start. Nutritional status as assessed by mBMI remained relatively stable during long-term tafamidis treatment, which is consistent with published analyses by Suhr et al [33], and lends further support for the long-term efficacy of tafamidis in slowing disease progression.…”
Section: Discussionsupporting
confidence: 88%
“…In 2014, Suhr et al [ 19 ] published a post hoc analysis of a more detailed account of the impact of tafamidis on nutritional status of patients with TTR-FAP enrolled in clinical trials. mBMI was used as a physiological indicator for treated patients as it is closely related to the duration of gastrointestinal disturbances, malabsorption, and survival after LT [ 19 ].…”
Section: Post Hoc Analyses Of Tafamidismentioning
confidence: 99%
“…For previous trials, mBMI was calculated as the product of the BMI and serum albumin concentration [ 19 ]. Height, weight, and albumin were measured during the baseline visit, and weight and serum albumin were measured every 6 months up to month 30.…”
Section: Post Hoc Analyses Of Tafamidismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by month 30 (completion of the open-label extension), placebo patients with 12 months of tafamidis treatment and tafamidis-treated patients with 30 months of treatment both tended to increase mBMI (28 ± 19 kg/m 2 g/l and 16 ± 18 kg/m 2 g/l, respectively). They concluded that mBMI is appropriate to monitor disease progression in patients with TTR-FAP and treatment with tafamidis can maintain or improve nutritional status [54] .…”
Section: Stabilizers Of Ttr Tetramers: Tafamidis and Diflunisalmentioning
confidence: 99%